Who Benefited More From the Developmental Education Reform in Florida? The Role of Exemption Status - Kai Zhao; Christine G. Mokher; Toby J. Park-Gaghan; Shouping Hu (SAGE Publishing, 2022)
Under Florida's developmental education (DE) reform since 2014, recent public high school graduates and active-duty military personnel became exempt from DE and traditional placement tests. The legislation also required colleges to provide accelerated instruction strategies for students remaining in DE and offer enhanced advising and support services for all incoming students. Focusing on the differential policy impacts on exempt and nonexempt students, we used statewide administrative data to examine changes in first-year completion rates for gateway math and English courses before and after the reform. Overall, and for those deemed to be college-ready, nonexempt students benefited more from the reform; however, the opposite is true for students who were not college-ready, with exempt students benefiting more. This study confirms that each component of the reform has played a role in contributing to its success.